Variation of Nutrient Intake and Digestibility in Jersey Crossbred Cattle at Various Physiological Stages and Production Levels - Vipin; Santra, Ashok; Tripura, Sachin; Prabhakar (Indian Journal of Animal Nutrition, 2023)
To compare the nutrient intake and digestibility of thirty-six (lactating, n=12; non-lactating pregnant, n=8; heifers aged >1.5 years up to first conception, n=8; and calves aged under 3month-1.5 years, n=8) Jersey crossbred cattle (Jersey × Red Sindhi × Tharparkar) at various physiological stages and production levels, a digestibility trial of seven days was conducted. Lactating cows were again divided based on their production levels into two groups. Group A had animals with average milk production of 5.5±0.40 kg/ d (range 4-7.99 kg/d). Group B had animals with average milk production of 11.1±0.40 kg/d (range 8-12 kg/ d). Total dry matter intake (%), acid detergent fiber digestibility (%) and dry matter intake (%) from straw and fodders were significantly (P<0.05) higher for the calves aged under 3month-1.5 years. Dry matter intake and ether extract digestibility (%) was significantly (P<0.05) higher for heifers aged >1.5 years up to first conception. Total dry matter intake (kg/d), and dry matter intake (%) from concentrate were significantly (P<0.05) higher for the lactating cows. Total dry matter intake (%) and dry matter intake (%) from concentrate were significantly (P<0.001) higher for group B as compared to group A cows. Based on the findings of this study, it can be concluded that heifers aged >1.5 years up to first conception and highyielding cows are better utilizers of nutrients from the diet.